Regulation of cholesterol synthesis in rat adrenal gland through coordinate control of 3-hydroxy-3-methylglutaryl coenzyme A synthase and reductase activities. - Balasubramaniam, S (1977)
The activities of cytosolic 3-hydroxy-3-methylglutaryl coenzyme A synthase [3-hydroxy-3-methylglutaryl-CoA acetoacetyl-CoA-lyase (CoA-acylating), EC 4.1.3.5] and microsomal 3-hydroxy-3-methylglutaryl coenzyme A reductase[mevalonate:NADP+ oxidoreductase (CoA-acylating), EC 1.1.1.34], two sequential enzymes in the cholesterol biosynthetic pathway, were shown to be regulated coordinately in the adrenal gland of the rat. When the plasma cholesterol level was lowered by administration of 4-aminopyrazolopyrimidine, a treatment known to enhance cholesterol synthesis in the adrenal, synthase activity in the gland rose by 14- to 29-fold and reductase activity rose by 50- to 100-fold. The subsequent intravenous infusion of low density lipoprotein restored the plasma cholesterol level and suppressed synthase and reductase activities in parallel. The activities of adrenal 3-hydroxy-3-methylglutaryl coenzyme A synthase and reductase were also shown to exhibit a coordinate pattern of diurnal variation with peaks in both enzymes achieved at the mid-point of the dark cycle. The activity of adrenal acetoacetyl coenzyme A thiolase (acetyl CoA acetyltransferase; acetyl-CoA:acetyl-CoA C-acetyltransferase, EC 2.3.1.9), the enzyme preceding the synthase in the cholesterol biosynthetic pathway, and the activity of adrenal mevalonate kinase (ATP:mevalonate 5-phosphotransferase, EC 2.7.1.36), the enzyme following the reductase, were not enhanced by cholesterol deprivation, and neither exhibited a pattern of diurnal variation. The coordinate control of 3-hydroxy-3-methylglutaryl CoA synthase and reductase in rat adrenal gland provides a model system to study the biochemical mechanism for the regulation of cholesterol synthesis in a tissue that uses cholesterol for the synthesis of steroid hormones.